Internal Migration Propensity Index (i-MPI) Toolkit for Guatemala and Honduras: A tool to estimate the household-level likelihood of domestic migration - Ceballos, Francisco; Hernandez, Manuel A.; Hernandez, Alvaro Espinoza (International Food Policy Research Institute, 2023)
The i-MPI aims to objectively measure and track the probability of individuals in a household of permanently migrating to a different location within their country, based on a small subset of household indicators and conditions that highly correlate with the (latent) decision to migrate domestically and, combined, best predict internal migration at the household level. The i-MPI avoids questions about migration intentions, which may be culturally sensitive, prone to misreporting, and difficult to monitor over time. Alternatively, it relies on a concise, reliable, and statistically-robust scoring index obtained from indirect indicators highly associated with migration decisions that are simple and easy to collect in the field.